Effect of intranasal insulin on perioperative cognitive function in older adults: a randomized, placebo-controlled, double-blind clinical trial - Sun, Miao; Ruan, Xianghan; Zhou, Zhikang; Huo, Yuting; Liu, Min; Liu, Siyuan; Cao, Jiangbei; Liu, Yan-Hong; Zhang, Xiaoying; Ma, Yu-Long; Mi, Weidong (Age and ageing, 2024)
Postoperative cognitive impairment are common neural complications in older surgical patients and exacerbate the burden of medical care on families and society. A total of 140 older patients who were scheduled for elective orthopaedic surgery or pancreatic surgery with general anaesthesia were randomly assigned to Group S or Group I with a 1:1 allocation. Patients in Group S and Group I received intranasal administration of 400 μL of normal saline or 40 IU/400 μL of insulin, respectively, once daily from 5 minutes before anaesthesia induction until 3 days postoperatively. Perioperative cognitive function was assessed using the Mini-Mental State Examination (MMSE) and Montreal Cognitive Assessment-Basic (MoCA-B) at 1 day before and 3 days after surgery and postoperative delirium (POD) incidence was assessed using the 3-minute Diagnostic Interview for CAM (3D-CAM) on postoperative days 1-3. Serum levels of interleukin-6 (IL-6), tumour necrosis factor α (TNF-α), S100-β and C-reactive protein (CRP) were measured on the first day after surgery. Insulin treatment significantly increased postoperative MMSE and MoCA-B scores in group I than in group S (P < 0.001, P = 0.001, respectively), decreased the incidence of POD within the 3-day postoperative period in Group I than in Group S (10.9% vs 26.6%, P = 0.024), and inhibited postoperative IL-6 and S100-β levels in Group I compared to Group S (P = 0.034, P = 0.044, respectively). Intranasal insulin administration is thus suggested as a potential therapy to improve postoperative cognition in older patients undergoing surgery. However, a more standardized multi-centre, large-sample study is needed to further validate these results.